2021
DOI: 10.1111/dom.14413
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of intramyocellular and extramyocellular fat by magnetic resonance imaging in subjects with diabetes, prediabetes and normoglycaemic controls

Abstract: Aim: To evaluate the distribution of intramyocellular lipids (IMCLs) and extramyocellular lipids (EMCLs) as well as total fat content in abdominal skeletal muscle by magnetic resonance imaging (MRI) using a dedicated segmentation algorithm in subjects with type 2 diabetes (T2D), prediabetes and normoglycaemic controls. Materials and Methods: Subjects from a population-based cohort were classified with T2D, prediabetes or as normoglycaemic controls. Total myosteatosis, IMCLs and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Myosteatosis is an ectopic fat bank that increases with age. Lipid deposition in skeletal muscle leads to the accumulation of lipid intermediates (diacylglycerol and ceramide) and destroys the insulin signaling pathway, leading to insulin resistance (IR) and the development of type 2 diabetes ( 48 , 50 , 51 ). In addition, researchers have found that there is a positive correlation between abdominal adipose tissue and the homeostasis model assessment of insulin resistance (HOMA-IR) in elderly white men without diabetes ( 52 ) and a negative correlation with insulin sensitivity ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myosteatosis is an ectopic fat bank that increases with age. Lipid deposition in skeletal muscle leads to the accumulation of lipid intermediates (diacylglycerol and ceramide) and destroys the insulin signaling pathway, leading to insulin resistance (IR) and the development of type 2 diabetes ( 48 , 50 , 51 ). In addition, researchers have found that there is a positive correlation between abdominal adipose tissue and the homeostasis model assessment of insulin resistance (HOMA-IR) in elderly white men without diabetes ( 52 ) and a negative correlation with insulin sensitivity ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of improving systemic glucose metabolism, consistent with previous studies, we found that gAd significantly reduced blood glucose levels and improved impaired glucose tolerance in high-fat diet mice, which is in agreement with the improvement of glucose metabolism by aerobic exercise. 37 , 38 Additionally, muscle lipid deposition is considered to be an important determinant of insulin resistance in skeletal muscle, 39 , 40 since increases in intramyocellular lipid and intermyocellular adipose tissue are associated with impaired skeletal muscle insulin signaling. Our study found that either exercise or gAd intervention reduced lipid ectopic deposition in the quadriceps muscle of mice and that SESN2 was involved.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for our pilot study was set according to that in previous studies that used an exploratory case study of fat distribution among older adults [ 30 , 31 ]. The exclusion criteria were: diseases that affect fat distribution and/or physical performance [ 32 , 33 , 34 ]; a clinical history of diabetes mellitus, heart disease (myocardial infarction, congestive heart failure, and angina pectoris), cerebrovascular disease (stroke, cerebral infarction, and cerebral hemorrhage), Parkinson’s disease, or previous hip and knee replacements; and patients with contraindications for magnetic resonance imaging (MRI). The participants underwent dual-energy X-ray absorptiometry (DXA), MRI, and 1 H-MRS to assess their body fat distribution and body composition.…”
Section: Methodsmentioning
confidence: 99%